IMPLEMENTASI KEBIJAKAN LINGKUNGAN HIDUP DI PROVINSI RIAU TAHUN 2014-2017 - Agus Khoirul Huda; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The environment as a gift and mercy from the Almighty God to the people and nation of Indonesia is a space for life in all aspects and dimensions in accordance with the insight of the archipelago. But the growth and development of the industry in Riau Province every year is increasing, resulting in pollution and environmental damage in the industrial area of Riau Province from year to year the accumulation is always increasing. Based on the description of the background of the problem, the author makes a problem statement, namely: How is the implementation of government policies on the environment in Riau Province in 2014-2017 and what are the obstacles to implementing government policies on the environment in Riau Province in 2014-2017, with the aim This study is: Describing government policy on environmental safeguards in Riau Province in 2014-2017. This research was conducted using secondary data (data that has been collected and analyzed by others) through literature studies from books, scientific research, newspaper articles and electronic news. This research was conducted in Riau Province. Riau Province was chosen as the location of the study because of frequent cases of environmental pollution. This research was conducted with qualitative analysis. Qualitative analysis is carried out if the empirical data obtained is qualitative data in the form of a collection of words and not a series of numbers and cannot be arranged in classification categories / structures. Based on the results of research and discussion it can be concluded that the implementation of government policies on the environment in Riau Province in 2014-2017 can be said to have not been realized, this is seen from the pollution that occurred in Riau Province since 2014-2017 continues to increase every year, such as fires forests and land (peat) are still an annual disaster, and in watersheds (DAS) in critical conditions result in water quality status of 4 heavily polluted rivers. Keywords: Policy Implementation, Environment.